2014
DOI: 10.1016/j.jval.2014.08.436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adverse Drug Reaction (ADR) Monitoring and Reporting System in China

Abstract: A 7 1 9 -A 8 1 3 A791 females. The average age in this group of patients was found to be 34.22 + 14.26. The average pre-hospitalization period was 1.58 + 2.07 days. Among them majority of the cases were suicidal (94.5%). Patients with a poison severity score of grade 1, 5.8% had intermediate syndrome. In grade 2 only 33.3% had intermediate syndrome and the most was seen in grade 3 where 60% had intermediate syndrome. Patients with a poison severity score of grade 1 only 10.6% were on ventilation, in grade 2 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study in Vietnam showed that few healthcare workers were interested in new ADRs and serious ADRs (52.7% and 56.3%, respectively), although these are priority ADRs for voluntary reporting systems. 62 In particular, the ADR reporting rate described in the literature was very low (24.2%), possibly because most healthcare workers considered these ADRs too common to report. 62 The availability of drug information has significantly improved for healthcare professionals in recent years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study in Vietnam showed that few healthcare workers were interested in new ADRs and serious ADRs (52.7% and 56.3%, respectively), although these are priority ADRs for voluntary reporting systems. 62 In particular, the ADR reporting rate described in the literature was very low (24.2%), possibly because most healthcare workers considered these ADRs too common to report. 62 The availability of drug information has significantly improved for healthcare professionals in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…62 In particular, the ADR reporting rate described in the literature was very low (24.2%), possibly because most healthcare workers considered these ADRs too common to report. 62 The availability of drug information has significantly improved for healthcare professionals in recent years. With the advancements in technology and the widespread use of the internet, healthcare professionals now have easier access to a wealth of drug-related information.…”
Section: Discussionmentioning
confidence: 98%
“…Second, constructing an effective regulation system to eliminate counterfeit and inferior drugs has become a research highlight for scholars. In recent years, China's adverse drug reaction (ADR) monitoring system has functioned well, but it also needs to enhance risk control actions to improve drug safety [17]. Donelan et al [18] analyzed the main factors of drug quality from the perspective of regulatory and cleaner production.…”
Section: Related Literaturesmentioning
confidence: 99%